Understanding child, family, environmental and agency risk factors: findings from an analysis of significant case reviews in Scotland. Issue 2 (19th April 2016) - Vincent, Sharon; Petch, Alison
Abstract: This paper presents the findings from an analysis of 56 significant case reviews (SCRs) in Scotland. In contrast to England and Wales where national analyses have been undertaken for many years, until this study was undertaken, the findings from SCRs had not previously been collated nationally. The paper discusses child, parent, environmental and agency factors that were identified in the SCRs and, whilst noting that the pathways to death or harm will be unique in individual cases, tries to further our understanding of the ways in which these different factors may interact to result in death or harm. A significant finding was the high number of SCRs that relate to the care and protection of children living in families whose lives are dominated by drug use and the associated issues this brings, including criminality and neighbourhood problems. Another challenging finding was the lack of suitable resources for the placement and support of troubled teenagers. Finally, a number of SCRs involved long‐term neglect and/or sexual abuse of school or nursery age children who had been known to statutory services for many years.